Murder most foul a panorama of social life in Melaka from the 1780s to the 1820s - Fernando, Radin (Monographs of the Malaysian Branch, Royal Asiatic Society, 2006)
This book presents a tapestry of social history of Melaka rich in detail as never before, using the court records from the 1780s through to the 1820s serendipitously preserved. Through the eyes of Dutch judges who carefully recorded crimes committed in the town, Radin Fernando weaves a fascinating narrative of social history of ordinary people caught in the most serious of all crimes, murder, as both perpetrators and victims. The speak for themselves, revealing their anxiety, anguish, humour and mischief, feelings common in human life but rarely encountered in history books, projecting a lively picture of the life of ordinary people in Melaka.